The Role of the Youth Generation in Strengthening Character Education, Nationalism, and the Preservation of Local Wisdom - Puspoko Jati, Dionisius Heckie; Listiarum, Febri; Aprilia, Harlis (Jurnal Pendidikan dan Pengajaran, 2025)
The rapid pace of globalization has resulted in a decline in the younger generation's concern for the values of nationalism and the preservation of local wisdom. In addition, the lack of active involvement of the younger generation in character education efforts and the preservation of traditional culture widens the gap between expectations and reality in the formation of national identity. This study aims to analyze and evaluate the role of the younger generation in strengthening nationalism-based character education while preserving local wisdom as a strategy for forming the nation's cultural identity. This research uses qualitative research with a case study design. The research subjects consisted of 40 youths as the main informants. Data collection methods included interviews, observations, and documentation, with instruments in the form of interview sheets, observation sheets, and documentation sheets. Data were analyzed using qualitative descriptive analysis through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the active participation of the younger generation in character-based education and local culture preservation is able to strengthen their love for the country, preserve traditional arts such as kuda lumping, wayang, and ketoprak, and foster their responsibility as successors to the nation's culture. Thus, it can be concluded that the younger generation plays a strategic role in internalizing the value of nationalism and preserving local wisdom so that it remains alive in the midst of modernization. The implication of this research is the need to develop character education programs based on local cultural.